Soft Tissue Myxoma - A Case Report - Sanjib Kumar Khataniar; Vaishali Keluskar (Wolters Kluwer Medknow Publications, 2004)
Myxoma of bone is a benign neoplasm commonly found in the maxillofacial region These myxomas of bone are considered by Stout as true neoplasms. Odontogenic or central myxomas are common as compared to soft tissue myxoma. Soft tissue myxomas are deeply situated in the skin or in the subcutaneous tissue but very few cases of intra oral soft tissue myxoma are documented and very little information is available.